Results of experimental infection of vaccinated and non-vaccinated ducklings with duck hepatitis virus - A. A. Chesnokova; E. V. Ivanova; V. V. Pronin; O. A. Chupina; V. Yu. Fomenko; M. S. Volkov; V. N. Irza (Ветеринария сегодня)
Duck virus hepatitis, a highly contagious disease occurring in ducklings, is currently reported in all countries with duck breeding industry. This infection is included in the list of notifiable diseases of the World Organization for Animal Health, restrictive measures are established and the regionalization of the country’s territory is carried out in case of its occurrence. Timely vaccination of parent flocks in order to obtain immune offspring takes a priority place in the system of anti-epidemic measures. Due to active development of duck breeding industry and increasing number of backyard farms, the need for high-quality and effective prevention tools for this infectious disease is growing. To date, one domestic native vaccine produced by FGBI «ARRIAH» and registered in the Russian Federation is available in native form and is intended for parenteral use. In order to extend the vaccine’s shelf life and for storage and transportation convenience, a live freeze-dried vaccine against duck virus hepatitis is being developed. The paper presents results of studying the pathogenesis of duck virus hepatitis and evaluating the efficacy and safety of the vaccine under development. Pathomorphological studies carried out post experimental infection indicate that duck hepatitis virus induces pathogenic effect not only in birds’ digestive organs (the liver, in particular) but also causes degenerative changes in central and peripheral immune organs: in cloacal bursa, thymus and third eyelid gland, that may be manifested as deficiency of B- and T-cell immunity and requires further studies. It has been shown that in case of immunization of 3-day-old ducklings, the experimental vaccine induces antibody-mediated immune response, no harmful effect is produced on poultry if a tenfold dose is administered which indicates its safety, and the vaccine ensures protection against infection with a control virulent strain of hepatitis virus.